2022
DOI: 10.1002/bio.4413
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in ZnO nanostructure as a gas‐sensing element for an acetone sensor: a short review

Abstract: Air pollution is a severe concern globally as it disturbs the health conditions of living beings and the environment because of the discharge of acetone molecules. Metal oxide semiconductor (MOS) nanomaterials are crucial for developing efficient sensors because of their outstanding chemical and physical properties, empowering the inclusive developments in gas sensor productivity. This review presents the ZnO nanostructure state of the art and notable growth, and their structural, morphological, electronic, op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 147 publications
0
7
0
Order By: Relevance
“…By using the values of , it is possible to predict the preferential crystal growth direction of ZnO. According to the literature [ 10 , 72 , 73 , 74 ], the growth of ZnO crystals along the direction is the most reported. Nonetheless, Cho et al observed that when the triethyl citrate is used as a surfactant, a lateral growth of each spine along the six symmetric directions can be noted [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…By using the values of , it is possible to predict the preferential crystal growth direction of ZnO. According to the literature [ 10 , 72 , 73 , 74 ], the growth of ZnO crystals along the direction is the most reported. Nonetheless, Cho et al observed that when the triethyl citrate is used as a surfactant, a lateral growth of each spine along the six symmetric directions can be noted [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mishra et al [25] briefly highlighted a gas sensor device made from metal oxide semiconductors (MOS), and described their morphologies, essential influencing parameters, gas-sensing procedure, structural, electronic, and optical properties. This review also explored the difficulties in acetone determination for MOS (ZnO)based gas sensors.…”
Section: Overview Of Published Reviewsmentioning
confidence: 99%
“…This data shows the resistance of the sensor when exposed to air. And then the lid of the test system is covered, and an equivalent volume of liquid for the concentration of the gas to be tested is calculated by equation (1) [31], and the required amount of liquid is injected into the heated platform of the gas test box using a micro syringe, and is made to become a gas by heating, and a fan system ensures that the gas is uniformly distributed inside the test box. The target gas comes into contact with the sensor and the element responds and is characterized by a change in resistance measured in the test system.…”
Section: Fabrication and Performance Test Of Gas Sensormentioning
confidence: 99%
“…For n-type semiconductors, for reducing gases, the gas sensing response of the sensor is defined as ΔR/R g , where ΔR = R a -R g [32], and When the gas-sensitive semiconductor sensor begins to come into contact with the detected gas, the element begins to respond and this is indicated by a change in resistance measured in the test system. It takes time from the beginning of the element's response to the detected gas until the resistance has changed to a steady state value, which is defined as the time it takes for the resistance to reach 90% of its steady state value [31]. Similarly, the recovery time is the time it takes for the resistance of the element to recover to 90% of its original value after the measured gas has been released [31], and the shorter the response and recovery time, the better the performance of the semiconductor element.…”
Section: Fabrication and Performance Test Of Gas Sensormentioning
confidence: 99%
See 1 more Smart Citation